Chemical and Microbiological Quality of Broiler Meat Supplemented Fermented Pursalane (Portulaca oleracea L.) Flour in Commercial Diets - Simon Edison Mulik; Jublin Franzina Bale-Therik; Annytha Ina Rohi Detha (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
The aim of this research was to know the effect of supplemented fermented purslane flour (FPF) in diet on the chemical quality, and microbiology of broiler chicken meat. One hundred DOC were used in this research. This research used a completely randomized design with 5 treatments and 4 replications. The treatments were K0 = commercial diet without FPF, K1 = commercial diet + 2.5% FPF, K2 = commercial diet + 5% FPF, K3 = commercial diet + 7.5% FPF, and K4 = commercial diet + 10% FPF. The variables studied were water content, protein content, and cholesterol levels of meat and contamination of Salmonella sp. Data were analyzed using Analysis of Variance (ANOVA). The results showed that the supplemented fermented purslane flour in diet significantly affected the water content and protein content of meat, but it did not significantly affect the cholesterol meat levels and contamination of Salmonella sp. It was concluded that the supplemented of fermented purslane flour in broiler chickens with a level of 10% was the best level. At this level, chicken meat is produced with the lowest water content while the highest protein content.